Classification of Fields having Different Soil Moisture Content by SVM Technique using Bistatic Scatterometer - A. Pandey1, S. K. Jha2, K .P. Singh3; G. S. Yadav4, R. Prasad1 (Recent Research in Science and Technology, 2011)
In the present paper, the classification of four different fields having different soil moisture contents is done by Support vector machine (SVM) technique. The bistatic X-band scatterometer measurement were carried out for different soil moisture fields at HH- and VV- polarization. The scattering coefficient was found to increase with the soil moisture content, whereas, the nature of variation was observed opposite in HH- and VV- polarizations keeping soil roughness constant. The X-band bistatic scatterometer datasets are used for training and testing of the SVM. Our results show higher classification accuracy of SVM, even for the small size of the training data set. The present work confirms the classification ability of SVM technique to classify the fields having different soil moisture contents using bistatic scatterometer data.